"Godforsaken hole called … called …": place, nation, and spatial crisis in Beckett's fiction and drama. Issue 2 (2nd April 2016) - Graham, Alan
Abstract: This essay explores how the figuring of place throughout the fiction and drama of Samuel Beckett registers and critiques narratives of place in Irish nationalist discourse. The Irish place-names of Beckett's texts are read in relation to a toponymic re-territorialisation in post-independence Ireland, a process which enervated place identities synonymous with a Protestant culture and history. In this way, the essay argues that the celebrated "placelessness" of Beckett's work and the collapse of spatial agency experienced by his protagonists is informed by the construction of nation-space in the country of the author's early life. The preponderance of scatological place-names in the Beckett oeuvre is approached in these terms and read as a mode of resistance to the self-sacrifice to nation demanded in emplacement.